Eminent Pearsonians: Britishness, Anti-Britishness, and Canadianism - Champion, C. (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2005)
AbstractBritishness in mid-Twentieth century Canada is usually treated as a fading overseas tie, a foreign allegiance, or a mark of dependency and colonial immaturity. There is a tendency to assume a kind of Manichean division between pro-British and anti-British: either in favour of Canadian independence, or beholden to the British connection, and to draw too sharp a distinction between what was “British” and what was genuinely “Canadian.” However, a study of the Eminent Pearsonians – three generations of Canadians whose anglophilia and Canadianness were intermingled – suggests that they were neither purely anglophile nor quite anglophobe but a tertium quid. Britishness and Canadianism were far more interpenetrated than is commonly thought. The nationalism and internationalism of Pearson and his contemporaries adumbrated their adoptive English liberalism and British liberal imperialism. Indeed, Britishness was interwoven into the Canadianness of the actors, bit-players, and stage-hands of all classes, ethnicities and genders in the Canadian pageant. In the positive sense of the term, Canadianism was an excrescence of Britishness.